Leptospirosis: toward a better understanding of the environmental lifestyle of Leptospira - Davignon, Grégoire; Cagliero, Julie; Guentas, Linda; Bierque, Emilie; Genthon, Pierre; Gunkel-Grillon, Peggy; Juillot, Farid; Kainiu, Malia; Laporte-Magoni, Christine; Picardeau, Mathieu; Selmaoui-Folcher, Nazha; Soupé-Gilbert, Marie-Estelle; et al. (Frontiers in Water, 2023)
Leptospira is a complex bacterial genus which biodiversity has long been overlooked. In the recent years however, environmental studies have contributed to shed light on its original and current environmental habitat. Although very fragile bacteria in laboratories, Leptospira have been shown to successfully occupy a range of soil and freshwater habitats. Recent work has strongly suggested that biofilm formation, a multicellular lifestyle regulated by the second messenger c-di-GMP, might be one strategy developed to overcome the multiple challenges of environmental survival. Within the genus, a minority of pathogenic species have developed the ability to infect mammals and be responsible for leptospirosis. However, most of them have retained their environmental survival capacity, which is required to fulfill their epidemiological cycle. Indeed, susceptible hosts, such as human, suffer from various symptoms, while reservoir hosts stay asymptomatic and release bacteria in the environment. In this review, we discuss how c-di-GMP might be a central regulator allowing pathogenic Leptospira to fulfill this complex life cycle. We conclude by identifying knowledge gaps and propose some hypotheses that should be researched to gain a holistic vision of Leptospira biology.